Fatal Cerebral Phaeohyphomycosis Due to Curvularia lunata in an Immunocompetent Patient - Carter, Elliot (American Society for Microbiology, 2004)
Curvularia infections in humans are relatively uncommon despite the ubiquitous presence of this soil-dwelling dematiaceous fungus in the environment. Originally thought to be solely a pathogen of plants, Curvularia has been described as a pathogen of humans and animals in the last half-century, causing respiratory tract, cutaneous, and corneal infections. Only three previous cases of central nervous system involvement by Curvularia have been documented in the medical literature. We report a fatal case of cerebral Curvularia infection in which there was no known history of immunocompromise or prior respiratory tract or sinus infection in the patient.